A Survey on Technostress in the Brazilian Software Companies focusing on Impacts and Interventions - Reolon, Gustavo; Souza, Alinne C. Corrêa; Silva, Rodolfo A.; Marcon, Marlon; Ortoncelli, Andre; Souza, Francisco Carlos M. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248727, 2026)
Research Context: Technostress has become increasingly prevalent in the Information Technology sector, manifesting as cognitive overload, fatigue, and anxiety resulting from the intensive use of Information and Communication Technologies (ICTs). In software development companies, where technological dependence is high and deadlines are strict, technostress has a direct impact on professionals’ well-being and productivity.Scientific and/or Practical Problem: One of the critical challenges is understanding how technostress, driven by intensive and constant use of ICT, impacts professionals’ well-being and performance, which can lead to reduced productivity and inefficiencies in software development processes. Proposed Solution and/or Analysis: This study explores and summarizes the origins, impacts, and interventions of technostress by applying the RED/ICT Scale, gathering the perceptions of Brazilian IT professionals through an exploratory survey complemented with semi-structured interviews. Related IS Theory: The study is grounded in Socio-Technical Theory, which emphasizes the interaction between technological and social factors in the workplace, supporting an understanding of how ICT-related demands shape stress experiences. Research Method: We surveyed 86 professionals from Brazilian software development companies and conducted six semi-structured interviews, providing valuable insights into their perceptions and experiences. Summary of Results: The findings revealed a moderate impact on disbelief (42%), with concerns about excessive reliance on technology. Fatigue had the highest impact (73%), reflecting exhaustion and an increased workload. Anxiety averaged 55%, strongly linked to a lack of internet access (65%), rapid technological changes (58%), and demand overload (54%). Ineffectiveness scored lower (39%), but still indicated distraction and adaptation difficulties (45%). Interviews reinforced these results, highlighting constant pressure to stay updated and limited organizational support. Contributions and Impact to IS area: The main contribution of this work is to understand technostress in the Brazilian IT context, which software organizations can mitigate through interventions such as training, work-life balance policies, and psychological support.